Open Label Prospective Study to Evaluate the Efficacy of Filix Mas in the Treatment of Gastrointestinal Disorders Due to Worm Infestation in the Pediatric Age Group. (Advancements in Homeopathic Research, 2025)
Introduction Worm infestation refers to the invasion of parasitic  worms inside the digestive tract. Patients can be  asymptomatic or exhibit long-term effects like growth  retardation and malnutrition, while symptomatic  patients often present with gastrointestinal disorders. Description This study evaluates the efficacy of Filix Mas, a rare  remedy referenced in Boericke’s Repertory for worm  symptoms, especially with constipation. The study  analyzed treatment outcomes for gastrointestinal  disorders due to worm infestations in children by  administering Filix Mas 30 CH. Objectives • Clinical verification of Filix Mas symptoms. • Assessment of the therapeutic importance of  Filix Mas for worm infestations. • Evaluation of Filix Mas’s efficacy in managing  gastrointestinal disorders from parasitic worm  infestations. Methods This pilot study was conducted at Dr. Madan Pratap  Khuteta Homoeopathic Medical College, Jaipur, for  6 months. the study included 35 pediatric patients  with confirmed worm infestations via the Stool  Ova & Parasite Test. Factors such as age, sex, area,  hygiene, and helminth type were analyzed. Treatment  followed Hahnemannian Guidelines, with outcomes  measured using the Visual Analogue Scale (VAS)  and post-treatment O&P Test. Results Worm infestations were most common in children  aged 7-9 years, particularly in males and those from  rural areas with poor hygiene. Ascaris lumbricoides  was the most frequently diagnosed helminth.  Among the 35 patients, 8 (22.85%) showed markedimprovement, 19 (54.28%) moderate improvement,  6 (17.14%) mild improvement, and 2 (5.71%) no  change. Statistical analysis (Paired t-test) confirmed  significant improvement, with a 95% confidence  interval for the difference ranging from 2.62161 to  4.06410, rejecting the null hypothesis. Conclusion Filix Mas proved effectiveness in treating  gastrointestinal disorders from worm infestations,  with most patients showing significant improvement.  Further research with larger samples and diverse  populations is recommended. The study’s limitations  include its short duration and small sample size
Keywords: Ancylostoma duodenale; Ascaris lumbricoides; Filix mas; Gastro-intestinal disorders; Homoeopathy; O&P Test; Trichuris trichiura; Worm infestation